Assessment of fungicide-based control of sheath blight using mobile spraying equipment - Liu, Haifeng; Jang, Hyeong-Rok; Choi, Sungyu; Park, Soyoon; Choi, Jae-ha; Choi, Hyeongju; Park, Sung-Won; An, Wooman; Hong, Se-Woon; Sang, Hyunkyu (Frontiers in Agronomy, 2025)
Sheath blight, caused by the fungal pathogen Rhizoctonia solani, is one of the major diseases affecting rice, leading to significant yield losses. Unmanned aerial vehicle (UAV)-based fungicide spraying has emerged as an efficient method for disease control. In this study, the sensitivity of R. solani to six fungicides (florylpicoxamid, fludioxonil, flutolanil, ipflufenoquin, orysastrobin, and pencycuron) with different modes of action was tested in vitro. These fungicides were also tested in planta, when after exhibiting the highest efficacy, orysastrobin and flutolanil were then selected to evaluate efficacy at reduced concentrations using mobile spraying equipment (MSE). The results revealed that even at 1/4 of the original concentration, both fungicides were sufficient to control sheath blight. This study provides an optimized fungicide application method for controlling sheath blight using UAVs.